ECONOMIC BUBBLES: THEIR CHARACTERISTICS AND PRICE CALCULATION MODEL AFTER OVERCOMING A BIFURCATION POINT - Ревякин, Г. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
In this work was analysed and updated theoretical and methodological aspects of research of economic "bubble", as well as was discussed its nature, causes and patterns of functioning. Was offered the classification of economic "bubbles" and descriptive models of their operation with the price calculation after overcoming a bifurcation point.